Work-Hardening in Three-Dimensional Slip-Line Fields - Bish, R.L. (Engineering Transactions, 1996)
A slip-line field theory that includes rotational continuity, published in an earlier article and shown therein to lead to Hill’s equiangular net, is extended to include work-hardening. This object is achieved by applying a rule of work-hardening shown in another earlier article to lead to the load observed in plane-strain extrusion experiments, work hardening having been shown to make a substantial contribution. The three-dimensional slip-line field theory developed in the paper is applied to the problem of a tube drawn through a conical die. It is shown how the force necessary to hold the tube against the die and so to prevent wrinkling may be calculated.